Weaving the Geographies of Harris Tweed: An ethnography of the labour, technologies and branding of life on the loom - Phelan, Kieran (2021)
Harris Tweed is a cloth defined through its specific geography of production; it is a cloth handwoven by islanders at their homes in the Outer Hebrides. It is this evocative and romantically imagined craft working that is central to its promotion and appeal, and is central to the branded storytelling of the cloth. Consumers connect to, see and ‘learn’ of who makes it, how and where, in a compelling craft story which frames and roots the cloth to its people, places and craft work practices. Through an ethnographic exploration of life on the loom, this thesis explores the branded origin story of the cloth. Through the voices of those who weave, a hidden polyvocality of work is revealed situated within a complex political and cultural economy too often hidden by the brand; it beholds greater complexity than the brand stories told of it. Using the framework of origination, the thesis enlists the multiple weaving voices of ethnographic fieldwork to voice the hidden stories of the warp and the weft- that of the labour, technologies and branding of Harris Tweed- to explore the tensions and contradictions wrapped up within them. Particular reflection is afforded to the associative and dissociative practices of the presentation of place and craft work within the brand, and the connections and disconnections that exist between the promoted, romantic brand story of Harris Tweed, and the multiple, diverse and problematic stories of the weavers’ working lives on the loom.